Behavioral and Experimental Economics and Financial Behavior: A Cross-Country Comparative Study - ERGÜN, Kutlu (Theoretical and Practical Research in Economic Fields; Vol 16 No 3 (2025): TPREF, Volume XVI, Issue 3(35), Fall 2025DO - 10.14505/tpref.v16.3(35).09, 2025)
One of the key objectives of financial literacy studies is to translate financial knowledge into positive financial behavior. Thus, appropriate financial choices and sound decisions can be made. However, this translation is hindered by psychological factors. This study examines the factors that influence financial behavior in both theoretical and practical contexts through the lenses of behavioral and experimental economics. This research seeks to examine the financial behaviors of university students in Romania, Türkiye, and Ukraine, as well as the factors affecting them from this perspective. The data were analyzed using multiple regression and the Mann-Whitney U. The findings revealed that Turkish students’ financial behavior level is higher than their counterparts in Romania and Ukraine. It was found that having financial knowledge improves positive financial behavior. The results indicate a potential relationship between the financial behavior level and the principles of behavioral and experimental economics. It was concluded that rational decision-making, along with trust, can foster positive financial behavior. This study may motivate educational authorities to implement financial education, as it underscores the beneficial impact of financial knowledge on financial behavior. Given that the research highlights the importance of trust, it could assist market makers in fostering sustainable market trust.